Auditory temporal order and speech perception in late talkers - Fatma Yurdakul Çınar; Ayça Çiprut (The Egyptian Journal of Otolaryngology)
Abstract Background Auditory temporal processing skills to perceive rapid changes in intensity, duration, and frequency of sounds over time are essential for early spoken language acquisition and speech perception. This study aimed to assess auditory temporal order and speech perception in late talkers. Methods Fifty children (25 with late-talking and 25 with typical development) aged 7 to 9 years were included in the study. All subjects had typical audiometric thresholds between 125 Hz and 8 kHz (≤ 20 dB HL) and no middle ear pathology. The frequency pattern test, duration pattern test, and speech intelligibility tests in quiet and noise conditions were used to assess auditory temporal order and speech perception. Results Late talkers performed lower than typically developing children on tests of frequency pattern, duration pattern, and speech intelligibility in noise (p < 0.05). When the correlations between the tests used were calculated, there were correlations between the tests for both groups. Conclusions The results indicate that children who talk later than their typically developing peers in the early years of life may have difficulties with some auditory processing skills, even if they catch up with their typically developing peers in speech and language skills in middle childhood. Thus, it is very crucial to monitor auditory processing skills as well as speech and language skills in late talkers.